Clinical significances of Bishop score and vaginal bleeding to controlled‐release dinoprostone delivery system (PROPESS) efficacy for cervical ripening: A retrospective single‐center study in Japan. Issue 4 (6th February 2023) - Imai, Kenji; Aoki, Chieko; Tano, Sho; Iitani, Yukako; Nakamura, Noriyuki; Ushida, Takafumi; Kajiyama, Hiroaki; Kotani, Tomomi
Abstract: Aims: To evaluate the effect of vaginal bleeding on the efficacy of controlled‐release dinoprostone delivery system (PROPESS) for cervical ripening and the factors affecting the PROPESS efficacy in a Japanese clinical setting. Methods: A total of 100 term pregnant women in whom PROPESS was used due to an unfavorable cervix (Bishop score ≤ 6) were enrolled. We retrospectively investigated which factors, including vaginal bleeding, were associated with the success of cervical ripening using logistic regression analysis. Moreover, the effect of vaginal bleeding on vaginal acidity was examined in 24 selected cases (control, 11; rupture of membrane, 4; and vaginal bleeding, 8). Results: A 25 women successfully ripened the cervix (effective group), and 75 were unsuccessful (noneffective group). Bishop score at insertion (adjusted odds ratio: 1.87; 95% confidence interval: 1.23–2.86; p  = 0.004), and vaginal bleeding at PROPESS insertion (adjusted odds ratio 6.63; 95% confidence interval 1.21–36.36; p  = 0.029) affected cervical ripening success. The cases with vaginal bleeding showed a significantly higher vaginal pH than the control cases (median value: 6.75 and 5.0, respectively). We identified no obvious adverse outcomes, such as tachysystole, fetal heart rate abnormality, or low Apgar/pH, associated with vaginal bleeding at insertion. Conclusions: Our findings suggest that the PROPESS efficacy depends on Bishop score at insertion and that vaginal bleeding at PROPESS insertion might have a significantly positive effect on cervical ripening in term pregnant women.